(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The main purpose of the present study is to analyze and forecast the dynamics of the real GDP of Bulgaria and to estimate the influence of the factor of seasonality. The dynamics and the seasonal fluctuations of the real GDP of Bulgaria have been studied by means of statistical models. A comparative analysis between Bulgaria and the European Union (EU-28) has been made. A conclusion has been reached that the factor of seasonality exerts a greater influence on the dynamics of the GDP in Bulgaria in comparison with the economy of the European Union as a whole.